Literacy Habituation as a Strategy for Developing Early Reading Skills: A Qualitative Case Study in Kindergarten Education - Ismujiasih, I; Zulkarnaen, Z (Universitas Muhammadiyah Surakarta, 2025)
Reading skills as an element of early childhood basic literacy remain a challenge in Indonesia, primarily because most previous studies have emphasized the use of specific learning media, rather than routine and contextual literacy habits as a strategy to improve reading skills. To address this gap, this study aims to describe the implementation of literacy habits through the Kawal Pagi program and its contribution to early childhood reading skills. This study used a qualitative approach with a case study design at ABA 5 Kindergarten in Salatiga. The research subjects consisted of 36 children from group B, two teachers, one principal, and six parents. Data were collected through participant observation, semi-structured interviews, and documentation, then analyzed using the Miles, Huberman, and Saldaña model through a process of reduction, presentation, and conclusion drawing. The findings indicate that daily literacy habits have a significant impact on the development of early reading skills. A total of 91.7% of children were able to recognize letters, 86.1% demonstrated phonemic awareness, 83.3% understood letter-sound relationships, and 75% were able to read simple words. Furthermore, 97.2% of children demonstrated an increased interest in reading, demonstrated through independent book selection and initiatives to interact with texts in their surroundings. The effectiveness of this activity was supported by the teacher's role as a facilitator, a text-rich classroom environment, and parental involvement. This research highlights the importance of literacy habituation as an alternative strategy to strengthen early childhood reading skills that does not rely on a single medium, but rather through natural and enjoyable routines. The implementation of the Kawal Pagi program can be recommended for early childhood education institutions as a model for strengthening a culture of literacy, with the caveat that there is a need to develop a variety of activities, provide a wider variety of reading materials, and increase parental participation to optimize learning outcomes.